PENINGKATAN LITERASI DIGITAL DAN KEAMANAN DATA PRIBADI PADA MASYARAKAT DESA MELOAK SEPAKAT, KABUPATEN GAYO LUES - Rahyul Amin; Ulil Amna; Fachrizal; Tisna Harmawan (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2025)
The rapid development of digital technology requires society to possess digital literacy skills and awareness of personal data security. However, many people still do not understand how to use technology safely. This community service activity aims to improve the understanding of the residents of Meloak Sepakat Village regarding digital literacy and personal data protection. The methods used include socialization, demonstration, and hands-on practice in setting privacy on devices and digital applications such as Google Chrome. The target participants are the general public, particularly teenagers, students, and village officials.The results of the activity indicate an increase in public awareness of the importance of protecting personal data, as well as basic skills in managing digital account privacy settings. In addition, small community groups were formed to act as digital literacy agents, disseminating information on digital security in a sustainable manner within the village.